2008
DOI: 10.1016/j.jmr.2008.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Pulse sequence for dynamic volumetric imaging of hyperpolarized metabolic products

Abstract: Dynamic nuclear polarization and dissolution of a (13)C-labeled substrate enables the dynamic imaging of cellular metabolism. Spectroscopic information is typically acquired, making the acquisition of dynamic volumetric data a challenge. To enable rapid volumetric imaging, a spectral-spatial excitation pulse was designed to excite a single line of the carbon spectrum. With only a single resonance present in the signal, an echo-planar readout trajectory could be used to resolve spatial information, giving full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
156
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 119 publications
(156 citation statements)
references
References 13 publications
0
156
0
Order By: Relevance
“…A spectral-spatial excitation pulse was designed according to (7). The RF pulse used was 13.6-ms long and has an excitation profile with two passbands with FWHM of 200 Hz, separated by a 1-kHz wide stopband with a suppression level of 10 −3 , and secondary bipolar sidelobes with suppression level of 10 −2 located 500 Hz from the primary passbands.…”
Section: Rf Pulse Design and Placement Of The Spectral Passbandmentioning
confidence: 99%
See 3 more Smart Citations
“…A spectral-spatial excitation pulse was designed according to (7). The RF pulse used was 13.6-ms long and has an excitation profile with two passbands with FWHM of 200 Hz, separated by a 1-kHz wide stopband with a suppression level of 10 −3 , and secondary bipolar sidelobes with suppression level of 10 −2 located 500 Hz from the primary passbands.…”
Section: Rf Pulse Design and Placement Of The Spectral Passbandmentioning
confidence: 99%
“…Recently, hyperpolarized 13 C pyruvate has been used to characterize cardiac metabolism noninvasively in the rat (4,5) and the pig (6). In these studies, [1][2][3][4][5][6][7][8][9][10][11][12][13] C] pyruvate was injected intravenously, and cardiac spectra were acquired with spatial localization to the heart either by coil location or by slice selection and single-step phase encoding of the field of view.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Work with several in vivo animal models has combined DNP with different imaging techniques (18)(19)(20)(21)(22), including chemical shift imaging (CSI) (23), to obtain metabolic maps of the heart using hyperpolarised [1-13 C]pyruvate (2,20,(24)(25)(26)(27). However, these studies have focused on in vivo models, with no work to date reported on the isolated perfused heart.…”
Section: Introductionmentioning
confidence: 99%